The challenges of implementing an integrated One Health surveillance system in Australia. (10th December 2017) - Johnson, I.; Hansen, A.; Bi, P.
Summary: As 75 per cent of emerging infectious diseases are of animal origin, a One Health approach that integrates the health of humans, animals and the environment could provide an earlier opportunity for zoonotic disease detection and prevention. In Australia, human, animal and ecological health are managed by separate sectors with limited communication. This study aims to explore how professionals in these fields perceive a One Health approach to zoonotic disease surveillance, aiming to identify the challenges to the implementation of an integrated system in Australia. Using a qualitative research method, ten semistructured interviews were conducted with academic experts to gain insight into the possibility of developing an integrated surveillance system in Australia. A thematic analysis of the data was undertaken. Findings showed the absence of a clear definition and subsequent vision for the future of One Health act as a barrier to interdisciplinary collaboration, and that siloed approaches by different sectors restrict the ability for professionals to work collaboratively across disciplines. An understanding of disease transmission was considered by participants to be a necessary requirement for a successful One Health approach. Finally, participants considered political will an essential requirement for the integration of surveillance systems. This study demonstrates that for a One Health approach to be implemented in an Australian setting, those working in the fields of human, animal and ecological health must agree on several aspects. The establishment of a formal governance body with representatives from each sector could assist in overcoming long‐standing barriers of privacy and distrust. Further, developing interdisciplinary training in One Health concepts for medical, environmental and veterinary students may encourage cross‐disciplinary collaboration. Finally, demonstrating to policymakers the economic benefit of improved and timely detection of zoonoses may help in facilitating a structured One Health approach to disease surveillance in Australia.